Comparison of Laparoscopic Versus Open Surgery for the Treatment of Ectopic Pregnancy: A Prospective Cohort Study - Abeera Sajid, Sofia Manzoor, Sadia Dilawar, Shazia Saaqib, Shaneela Sattar (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Ectopic pregnancy remains a significant cause of maternal morbidity and mortality, accounting for a large proportion of first-trimester complications. Objective: To compare the efficacy, safety, and postoperative outcomes of laparoscopic surgery versus open surgery n the treatment of ectopic pregnancy. Methods: This was a prospective cohort study conducted at the department of Obstetrics and Gynaecology, Lahore General Hospital, Lahore from June 2021 to November 2021. A total of 185 patients diagnosed with ectopic pregnancy were enrolled and allocated into two groups based on the surgical approach: Group A (n = 95) underwent laparoscopic surgery, while Group B (n = 90) underwent open laparotomy. The study aimed to compare intraoperative and postoperative outcomes between both techniques in terms of efficacy, safety, and recovery profile. Results: The mean operative time was slightly longer in the laparoscopic group (74.3 ± 18.2 min) than the open group (68.5 ± 15.9 min; p = 0.04). However, mean blood loss was significantly lower (96.4 ± 32.1 mL vs. 182.3 ± 40.6 mL; p < 0.001). Patients who underwent laparoscopy reported less postoperative pain (VAS 3.2 ± 1.1 vs. 5.8 ± 1.3; p < 0.001), shorter hospital stays (2.6 ± 0.9 vs. 5.4 ± 1.2 days; p < 0.001), and faster recovery (10.4 ± 3.1 vs. 17.2 ± 4.5 days; p < 0.001). The overall complication rate was lower in laparoscopy (6.3%) than open surgery (17.8%; p = 0.02). Conclusion: Laparoscopic surgery is a superior and safer alternative to open laparotomy for the treatment of ectopic pregnancy, providing significantly less blood loss, reduced pain, shorter hospital stay, and quicker recovery. It should be considered the preferred surgical approach in hemodynamically stable patients to enhance postoperative recovery and preserve reproductive potential. Keywords: Ectopic pregnancy, laparoscopy, laparotomy, minimally invasive surgery, postoperative outcomes